2015
DOI: 10.1108/lodj-01-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among applications of tacit knowledge and transformational/transactional leader styles

Abstract: Relationships among applications of tacit knowledge and transformational/transactional leader styles: an exploratory comparison of the MLQ and TKML:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…The mainstream theories considered included trait theory, behavioral theory, situational/context leadership, contingency, transactional and transformational theory. To begin the exploration of the leadership theories, each of these contemporary theories is unpacked and defined based on what is readily apparent and addressed in the extant literature (King, 1990; Taylor et al , 2015; Hunt and Fedynich, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mainstream theories considered included trait theory, behavioral theory, situational/context leadership, contingency, transactional and transformational theory. To begin the exploration of the leadership theories, each of these contemporary theories is unpacked and defined based on what is readily apparent and addressed in the extant literature (King, 1990; Taylor et al , 2015; Hunt and Fedynich, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Questionnaire Bass and Riggio (2006, p19) indicated that "the most widely accepted instrument to measure transformational leadership is the Multifactor Leadership Questionnaire (MLQ)". The reason why Bass' and Avolio's (1997) MLQ is applied to this study is their theory is the dominant assessment tool to distinguish leadership styles, measuring the constructs of transactional, transformational and laissez-faire leadership (Sudha, et al, 2016;Taylor, et al, 2015). Bessai (1995) suggested "one of the major strengths of the questionnaire seems to be the empirical support it provides for the new paradigm of leadership that distinguishes between transactional and transformational leadership.…”
Section: The Multifactor Leadershipmentioning
confidence: 99%
“…A total of 24 of the reviewed articles examined outcomes of passive and/or active forms of destructive leadership (Table 1). Eight of the studies (30%) examined performance (Bass, Avolio, Jung, & Berson, 2003;Bass & Yammarino, 1991;Chou, Sibley, Liu, Lin, & Cheng, 2015;Eid et al, 2008;Taylor, Psotka, & Legree, 2015) and effectiveness (Schiena, Letens, Van Aken, & Farris, 2013;Yammarino & Bass, 1990;Yammarino et al, 1993). Both active and passive forms of leadership were negatively related to scores on performance and effectiveness.…”
Section: Descriptive Findingsmentioning
confidence: 99%